ANALYSIS OF REGIONAL RESILIENCE IN THE NORTH SUMATRA SPORTS CENTER AREA DEVELOPMENT PLAN BASED ON GIS AND SWOT - Feby Milanie; Abdiyanto; Jimmy Karendi; Wirdatul Akmal; Novi Armen; Roldes Ricardo; Inas Suha Azzahra; George Nollan Zaro Zega (Bulletin of Engineering Science, Technology and Industry, 2026)
The development of the North Sumatra Sport Center in Batang Kuis Subdistrict, Deli Serdang Regency, is part of an effort to establish a new growth center that supports the enhancement of the region's physical, social, economic, and environmental resilience. The objective of this study is to analyze the region's resilience potential based on the development plan for the North Sumatra Sports Center, using a spatial approach based on Geographic Information Systems (GIS) and a SWOT analysis, with the aim of formulating sustainable and resilient regional development strategies. The research method used is a mixed-methods approach combining qualitative and quantitative analysis. Research data were obtained from spatial satellite imagery, area planning documents, observations, and literature reviews. GIS analysis was used to identify spatial structure, accessibility, land use, as well as the area's potential and vulnerabilities, while SWOT analysis was used to determine development strategies based on the region's internal and external factors. The research findings indicate that the North Sumatra Sport Center area holds strategic potential as a new economic growth hub through the integration of sports, business, education, and transportation functions based on the Transit-Oriented Development (TOD) concept. The area's key strengths lie in its regional accessibility, multimodal connectivity, and the presence of integrated supporting facilities. However, the area's development also faces challenges in the form of flood risks due to land-use changes, the potential for gentrification, and pressures on environmental quality. Based on the SWOT analysis results, the recommended priority strategy is to optimize the integration of the railway station with the business center and commercial areas to enhance the region's competitiveness, accompanied by strengthened spatial planning management, sustainable drainage systems, and the provision of green open spaces as a form of environmental mitigation. This study is expected to serve as a reference for the planning of integrated sports areas oriented toward the principles of sustainability and regional resilience.